A fatal case of peripartum cardiomyopathy. (June 2014) - Cohen, Ronny; Mallet, Thierry; Mirrer, Brooks; Loarte, Pablo; Gale, Michael; Kastell, Paul
Abstract Peripartum cardiomyopathy is a life-threatening cardiac condition affecting pregnant women either late in pregnancy or early in the post-partum period. The latest studies show a dramatic improvement in the mortality rates of women affected with this disorder, which has been correlated with advances in medical therapy for heart failure. However, patients continue to die of this condition. The following case report describes a typical patient with peripartum cardiomyopathy diagnosed on clinical grounds, along with echocardiogram findings of severe systolic dysfunction and global hypokinesis consistent with dilated cardiomyopathy. Emergency cesarean delivery had to be performed for fetal distress. There was significant improvement of the patient's condition with standard pharmacological management for heart failure at the time of discharge. However, five weeks after discharge, fatal cardiac arrest occurred. It is hoped that this article will raise awareness about this rare but potentially fatal condition and promote understanding of its main clinical features, diagnostic criteria, and conventional pharmacological management.